2017
DOI: 10.2147/cia.s129868
|View full text |Cite
|
Sign up to set email alerts
|

Which is preferable for orthostatic hypotension diagnosis in older adults: active standing test or head-up tilt table test?

Abstract: Background: Correct evaluation of orthostatic hypotension (OH) is crucial in geriatric practice, since OH is associated with mortality and morbidity. The study aimed to determine the most appropriate method for measuring blood pressure in transition from supine to upright position in order to diagnose OH in older adults. Methods: Active standing test (AST) and head-up tilt table (HUT) test as well as comprehensive geriatric assessment (CGA), including mini-mental state examination or the cognitive state test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 36 publications
0
33
0
1
Order By: Relevance
“…Studies finding an association of OH with ADL dependence did not include more patients with cognitive impairment than studies finding no association. The prevalence of dementia was 42.9% in one study reporting an association (Gaxatte et al, 2017) compared to 27.0-44.9% in three studies reporting no association (Aydin et al, 2017;Jodaitis et al, 2015;Siennicki-Lantz et al, 1999). The mean Mini Mental State Examination score was 17.6-25.8 points in four studies finding an Cs: cross-sectional; P: prospective; R: retrospective; OH: consensus definition of orthostatic hypotension; OH 30/15 : drop of 30 and 15 mmHg in systolic or mean blood pressure, respectively; OH+: OH with symptoms; iOH: initial OH (systolic blood pressure drop of at least 40 mmHg and/or a diastolic blood pressure drop of at least 20 mmHg within 15 s after standing); sOH: systolic blood pressure drop of at least 20 mmHg; NR: not reported; AS: active stand; SS: sit to stand; PS: passive sit; HUT: head up tilt; LBNP lower body negative pressure (i.e.…”
Section: Meta-analysismentioning
confidence: 83%
See 1 more Smart Citation
“…Studies finding an association of OH with ADL dependence did not include more patients with cognitive impairment than studies finding no association. The prevalence of dementia was 42.9% in one study reporting an association (Gaxatte et al, 2017) compared to 27.0-44.9% in three studies reporting no association (Aydin et al, 2017;Jodaitis et al, 2015;Siennicki-Lantz et al, 1999). The mean Mini Mental State Examination score was 17.6-25.8 points in four studies finding an Cs: cross-sectional; P: prospective; R: retrospective; OH: consensus definition of orthostatic hypotension; OH 30/15 : drop of 30 and 15 mmHg in systolic or mean blood pressure, respectively; OH+: OH with symptoms; iOH: initial OH (systolic blood pressure drop of at least 40 mmHg and/or a diastolic blood pressure drop of at least 20 mmHg within 15 s after standing); sOH: systolic blood pressure drop of at least 20 mmHg; NR: not reported; AS: active stand; SS: sit to stand; PS: passive sit; HUT: head up tilt; LBNP lower body negative pressure (i.e.…”
Section: Meta-analysismentioning
confidence: 83%
“…- Aydin et al, 2017 Balance; gait; ADL Tinetti balance score: 13.5 (OH-, SD 2.8), 13.2 (OH+, SD 3.2), p = 0.384. Tinetti gait score: 10.2 (OH-, SD 1.7), 10.1 (OH+, SD 1.8), p = 0.570.…”
Section: Outcome (O)mentioning
confidence: 99%
“…; Aydin et al . ), and HUT has been used to assess orthostatic tolerance in astronauts when they return to Earth from space (Buckey & Homick, ; Levin et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…When rabbits aged 3 or 4 weeks grew up under 20 deg HDT for ß5 weeks, the number of afferent unmyelinated fibres in the left aortic nerves decreased and the baroreceptor reflex gain was also reduced as HR/ BP, the whole nerve activities of afferents in response to BP changes were smaller . The head-up tilting (HUT) test is one of the health checks for orthostatic tolerance in humans (Hughson et al 1994;Akimoto et al 2011;Aydin et al 2017), and HUT has been used to assess orthostatic tolerance in astronauts when they return to Earth from space (Buckey & Homick, 2003;Levin et al 2003). We previously reported that BP decreased and HR increased during 3 min of HUT in unconscious and conscious rats, and that changes in HR based on the baroreceptor reflex in anaesthetized rats were not observed after sinoaortic denervation (SAD; Waki et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Schellong considered the responses in part (1) to depend on neurogenic regulation of peripheral blood vessels, part (2) on both neurogenic control of blood vessels and cardiocirculatory regulation, and part (3) on cardiac regulation only.…”
mentioning
confidence: 99%